Study of access template to graphics engine GM effect on the performance - RomanV. . Arzumanyan; Alexander I. Sukhinov (Advanced Engineering Research, 2016)
The work objective is to study the effect of the graphical processor unit computational cores load level and memory access pattern on the memory bus bandwidth and scaling acceleration. The research subject is the problem of scalability of the parallel computing performance and acceleration. The following hypothesis is checked: while processing images for multi-core shared-memory systems, Gustafson - Barsis’s law is more crucial than the memory access template at the underloading of the GPU cores. The research methodology is a computational experiment with further analysis of the obtained results. The conclusions are as follows. The suggested hypothesis is proved. For that, a series of experiments on various heterogeneous computational systems with OpenCL standard support is conducted. The application field of the results obtained includes the development of algorithms and software for the highly parallel computer systems. The memory access template starts to place certain restrictions on the algorithm efficiency only when the load level of the computational cores is sufficient. Video cards with the private memory show more stable results in comparison to those which share memory with the central processing unit.